2016
DOI: 10.2169/internalmedicine.55.6088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Visceral Fat Area Measured by Dual Impedance Method on the Diagnostic Components of Metabolic Diseases in a Middle-aged Japanese Population

Abstract: Objective The aim of this study was to examine the associations between the visceral fat area (VFA) and the subcutaneous fat area (SFA) as estimated by the dual impedance method with a body composition monitor (BCM) and the diagnostic components of metabolic syndrome in a middle-aged Japanese population. Methods The subjects included 303 men (average age 51.3±9.0 years old) and 345 women (average age 40.0±9.4 years old). The VFA and SFA were estimated by BCM, and the associations among the components of metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…Where more easily accessible modality at lower cost should be developed, the bioelectrical impedance analysis (BIA) has been recently developed, which is used in population and clinical studies as a technique to estimate body composition ( 15 19 ). Unno and colleagues ( 15 ) found that VFA estimated by BIA is useful for detection of metabolic syndrome (MetS), as consistently reported by other studies ( 16 20 ).…”
Section: Introductionsupporting
confidence: 58%
“…Where more easily accessible modality at lower cost should be developed, the bioelectrical impedance analysis (BIA) has been recently developed, which is used in population and clinical studies as a technique to estimate body composition ( 15 19 ). Unno and colleagues ( 15 ) found that VFA estimated by BIA is useful for detection of metabolic syndrome (MetS), as consistently reported by other studies ( 16 20 ).…”
Section: Introductionsupporting
confidence: 58%
“…VFA estimation by the dual bioelectrical impedance analysis used in the present study can be influenced by body shape or body water distribution 39. However, the dual bioelectrical impedance analysis for measuring VFA is well correlated with that of CT,19 20 and we used categorical information of VFA. Therefore, missing VFA classifications might occur less frequently.…”
Section: Discussionmentioning
confidence: 96%
“…BMI was calculated as weight (kg) divided by height squared (m 2 ). VFA was measured in the morning before breakfast by dual bioelectrical impedance analysis which is the first device in the world for measuring visceral fat without X-ray exposure (DUALSCAN; Omron Healthcare Co., Kyoto, Japan) 19–21. BP was measured using a sphygmomanometer after 5 min of rest.…”
Section: Methodsmentioning
confidence: 99%
“…Because a correlation between visceral fat mass and uric acid concentration in blood has been reported, 28,29) we measured uric acid, allantoin and blood urea nitrogen (BUN) in plasma. Allantoin and BUN showed significant dose-dependent decreases in the Ca-Alg groups.…”
Section: Discussionmentioning
confidence: 99%